The design of teaching materials as a tool in EFL teacher education: experiences of a Brazilian teacher education program - Eliane Hercules Augusto-Navarro (Ilha do Desterro)
This paper discusses how teaching material design can contribute to educate EFL teachers to consider their prospective students’ profile. This professional activity requires the student teachers to take a set of decisions, make choices and explain the reasons for them. The described practices in teacher education are carried at a public university in the southeast of Brazil and Larsen-Freeman's (1983) assertion that teaching is about making choices, which should be informed, is closely considered. The author describes three different contexts of practice and presents student teacher considerations about the experiences. There are challenges and gains in the process of teaching/learning how to design ELT materials, but as has been pointed out by the participants involved in this practice the gains are worth the challenges.